The possible therapeutic role of advanced glycation end-product inhibitors in ischemic stroke - Nada H. Aljarba; Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; Mustafa M. Shokr; Marios Papadakis; Athanasios Alexiou; Mubarak Alruwaili; Mohammed Alrouji; Mohammed S. Alshammari; Gaber El-Saber Batiha (Brain Research Bulletin)
The advanced glycation end-products (AGEs) are toxic molecules result from non-enzymatic interactions of sugar with lipids or proteins. AGEs promote the generation of reactive oxygen species that induce the release of pro-inflammatory cytokines, and alter the intracellular signaling leading to progressive biochemical and metabolic derangements. AGEs-induced cellular aging is implicated in the development and progression of different neurological disorders such as dementia, neuropsychiatric disorders, and cerebrovascular diseases. Particularly, AGEs-induced microangiopathy and macroangiopathy trigger the induction of prothrombotic/thrombotic cascades with subsequent increase risk of acute ischemic stroke (AIS). Many studies highlighted that AGEs serum levels are correlated with the incidence, pathogenicity, and severity of AIS. However, the relationship between AGEs and AIS is not elucidated completely. Therefore, this review aims to discuss how AGEs promote the development and progression of AIS, and how AGEs inhibitors could be effective in the management of AIS.